2011
DOI: 10.1002/cncr.27372
|View full text |Cite
|
Sign up to set email alerts
|

Extended field stereotactic radiosurgery for recurrent glioblastoma

Abstract: BACKGROUND: Stereotactic radiosurgery (SRS) is among the few therapeutic options for glioblastoma that recurs after standard radiation and chemotherapy, but its efficacy has been limited. METHODS: Since November 2007, the authors have modified the clinical target volume by adding a 0.5-to 1-cm margin to the gadolinium-enhanced area (extended field SRS), in contrast to conventional SRS using no margin to set the clinical target volume. A total of 35 recurred glioblastoma lesions in 9 patients were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 30 publications
3
28
0
4
Order By: Relevance
“…Although extended field stereotactic radiosurgery achieved high local tumor control rate, no significant survival benefit was achieved, with overall survival of 9 months compared with 10.5 months after conventional stereotactic radiosurgery (p = 0.83). 19) The overall survival after extended field stereotactic radiosurgery was also consistent with the results of only stereotactic radiosurgery for recurrent glioblastoma from other institutes at 5.3 to 13 months (median 10 months), 2,6,12,14,23,30,35,39) and apparently represent the limitation of survival benefit achieved by stereotactic radiosurgery for local treatment. In fact, six of seven patients who died after extended field stereotactic radiosurgery in our study, died of remote recurrence or dissemination (data not shown).…”
Section: Refinement Of Treatmentsupporting
confidence: 81%
See 2 more Smart Citations
“…Although extended field stereotactic radiosurgery achieved high local tumor control rate, no significant survival benefit was achieved, with overall survival of 9 months compared with 10.5 months after conventional stereotactic radiosurgery (p = 0.83). 19) The overall survival after extended field stereotactic radiosurgery was also consistent with the results of only stereotactic radiosurgery for recurrent glioblastoma from other institutes at 5.3 to 13 months (median 10 months), 2,6,12,14,23,30,35,39) and apparently represent the limitation of survival benefit achieved by stereotactic radiosurgery for local treatment. In fact, six of seven patients who died after extended field stereotactic radiosurgery in our study, died of remote recurrence or dissemination (data not shown).…”
Section: Refinement Of Treatmentsupporting
confidence: 81%
“…2) resulted in significant improvement of local control rate from 55% to 92%. 19) Local control might lead to improvement of performance status as achieved by surgical mass reduction, 1) but improvements in performance status associated with local control achieved by stereotactic radiosurgery remain unclear and further analyses are awaited. Although extended field stereotactic radiosurgery achieved high local tumor control rate, no significant survival benefit was achieved, with overall survival of 9 months compared with 10.5 months after conventional stereotactic radiosurgery (p = 0.83).…”
Section: Refinement Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, RTOG-RPA Class was determined in 95% of patients with the greatest survival advantage appreciated by patients in Class IV: 20.2 months (Table 2) (Figure 4). In prior studies recently reviewed [38], median overall survival for all patients treated with salvage GKRS was from 16.7 to 33.2 months [15,16,18,[30][31][32][33][34][35]. It is also informative to analyze which patient characteristics predict longer survival following salvage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery has also shown to provide a survival benefit for those in which repeat surgical resection is not indicated [29]. Multiple studies have offered evidence to support a survival benefit for select rGBM patients who receive GKRS salvage treatment [15,16,18,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%